STRATEGI MEMBELAJARKAN MATEMATIKA PADA SISWA LAMBAN BELAJAR KELAS VIII INKLUSI DI SMP PGRI 1 SAMPIT - Hidayati Shaliha, Nurul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
The objectives of this research wereto describe teacher strategy in teaching mathematics from the teacher’s ability in explaining in accordance with conceptual and procedural knowledge of 8th grade students of SMP PGRI 1 Sampit. This research is a qualitative descriptive using a single case study method, in depth study of learning system and mathematics learning in inclusive school.The subject of the research is mathematic teacher and slow learner student of the 8th grade from SMP PGRI 1 Sampit. The data of this research are information about the teacher strategy in learning Mathematics in the inclusive 8th grade.The research results showthe mathematics learning strategy in the inclusive 8th grade of SMP PGRI 1 Sampit observed from the teacher’s ability in explaining the subject in accordance with the delivering explanation indicators which are planning the explanation, clarity of delivering the explanation, the use of examples and illustrations, the use of intonation in delivering the explanation, and giving the feed back to the students. The teacher used Contextual Teaching and Learning (CTL) to teach the concept of mathematics and Discovery Learning methods to teach the procedure of mathematics.